Формирование компетенций учащихся в сфере психологической разгрузки и релаксации как путь модернизации образования - Крюков, С.Н. (My University, 2013)
In this work considered the actualization of inculcate in educational process of the course of psychology discharge and relaxing and the possibility structure of such course